(untitled) (Journal of Contemporary Studies, 2021)
The higher education institutions in Pakistan need to effectively utilize their capabilities to enhance organizational learning through IT-based infrastructure. This study examines the direct and indirect effects of knowledge management infrastructure and capabilities on organizational learning. To test the hypothesized relationships, data was collected from 250 respondents based on convenient sampling technique. The partial least square (PLS) structural equation modeling technique was applied for testing of hypotheses. The results revealed that IT-based knowledge management infrastructure is significantly related to organizational learning directly and through knowledge management capabilities. The study findings reinforced the need for the development of IT infrastructure in the service sector to enhance organizational learning.